Analysis of the Website Quality of the Regional Revenue, Finance and Asset Management Agency, Wonosobo Regency, Central Java Province - Nugraheni, Anindita Ayu; Nurnawati, Eem; Samuel, Helwani (Formosa Journal of Sustainable Research, 2024)
The implementation of e-government is one form of SPBE implementation in Indonesia. The Wonosobo Regency Regional Revenue, Finance and Asset Management Agency (BPPKAD) website with the link bppkad.wonosobokab.go.id is a form of public service innovation. However, in terms of implementation and management, the BPPKAD website is still not up to date with several features that cannot be accessed and the number of visitors is still minimal. Data collection was carried out using observation, interview and documentation techniques. The Wonosobo Regency BPPKAD website meets the three dimensions of website quality theory according to Alvaro Rocha, namely including 8 indicators, namely accuracy, relevance, completeness, updating, reliability, responsiveness, usability and accessibility. The inhibiting factors that occur in website management are lack of human resources, vulnerability to network disruption, and lack of public knowledge. Suggestions that can be made to overcome several problems are adding competent human resources in the IT field, especially in carrying out website management, optimizing website management by improving features that cannot be accessed and conducting outreach to the public regarding the use of the Wonosobo Regency BPPKAD website